IL-33/ST2 Activation Is involved in Ro60-Regulated Photosensitivity in Cutaneous Lupus Erythematosus - Yitian Song; Fangzhi Wei; Ying Liu; Feng Han; Lihui Ma; Yanping Zhuang; Chengdan Pan; Zhandong Jia; Aimin Gong (Mediators of Inflammation)
Interleukin- (IL-) 33 contributes to various inflammatory processes. IL-33/ST2 activation participates in systemic lupus erythematous via binding to the receptor of Suppression of Tumorigenicity 2 protein (ST2). However, whether IL-33/ST2 interferes with the nosogenesis of cutaneous lupus erythematosus (CLE) has not been reported so far. Herein, we proposed to disclose the impacts on IL-33/ST2 activation and Ro60 on CLE and their potential implications in the photosensitization of CLE cells. IL-33, ST2, and Ro60 in CLE patients’ skin lesions were detected. Murine keratinocytes stimulated with or without IL-33 were irradiated by ultraviolet B (UVB), and the levels of Ro60 and inflammation markers were determined. Keratinocytes were cocultured with J774.2 macrophages and stimulated with IL-33 for analysis of chemostasis. The results identified that IL-33, ST2, and downstream inflammation markers were significantly upregulated in CLE lesions with Ro60 overexpression. Additionally, IL-33 treatment promoted the upregulation of Ro60 induced by UVB treatment in murine keratinocytes. Moreover, IL-33 stimulates keratinocytes to induce macrophage migration via enhancing the generation of the chemokine (C–C motif) ligands 17 and 22. Meanwhile, the silencing of ST2 or nuclear factor-kappa B (NF-κB) suppression abolished IL-33-induced upregulation of Ro60 in keratinocytes. Similarly, the inhibition of SOX17 expression was followed by downregulation of Ro60 in keratinocytes following IL-33 stimulation. In addition, UVB irradiation upregulated SOX17 in keratinocytes. Conclusively, the IL-33/ST2 axis interferes with Ro60-regulated photosensitization via activating the NF-κB- and PI3K/Akt- and SOX17-related pathways.